Synthesis and antimicrobial evaluation with DFT study for new thiazole derivatives - Abbas, Sumayah Saadi; Kubba, Ammar A.Razzak Mahmood (Iraqi Journal of Pharmaceutical Sciences, 2018)
Two compounds,[2-amino-4-(4-nitro phenyl) 1,3-thiazole],(4) and [2-amino-4-(4-bromo phenyl) 1,3-thiazole],(5), were synthesized by refluxing thiourea (1) with each of para-ntiro and para-bomophanacyl bromides(2) and (3) respectively, in absolute methanol. Then, by reaction of [5] with 3,5-dinitrobenzoyl chloride in dimethylformamide (DMF) yielded (6) .On the other hand, reaction of (4) with chloroacetyl chloride in dry benzene afforded (7), which is upon treatment with thiourea in absolute methanol, afforded (8) . The characterization of the titled compounds were done utilizing FTIR spectroscopy, 1HNMR, CHNS elemental analysis and by measurements of their physical properties. The synthesized compounds had been screened for their, in vitro preliminary antimicrobial activity against four Gram positive bacteria (Staph. aureus, Micrococcus luteus, Bacillus subtilis and Bacillus pumilus), and four Gram negative bacteria (Pseud.aeroginosa, E.coli, Proteus mirabilis and Klebsiella pneumoniae)and three fungi species: (Saccharomyces cerevisiae, Candida Tropicalis and Candida albicans) using a minimum inhibitory concentration (MIC) of 100 µg\ml of derivative in dimethylsulfoxide, by well diffusion method.Compound (6) showed moderate antibacterial activity against some tested Gram positive bacteria (Bacillus pumilus and Bacillus Subtilis) and a moderate antifungal activity towards Candida albicans. Computational study was performed to calculate some of the thermodynamic parameters of synthesized derivatives by using density functional theory (DFT).